Profiling and Validation of Live‐Cell Protein Methylation with Engineered Enzymes and Methionine Analogues. Issue 8 (9th August 2021) - Weiss, Nicole; Seneviranthe, Chamara; Jiang, Ming; Wang, Ke; Luo, Minkui
Abstract: Protein methyltransferases (PMTs) regulate many aspects of normal and disease processes through substrate methylation, with S ‐adenosyl‐L ‐methionine (SAM) as a cofactor. It has been challenging to elucidate cellular protein lysine and arginine methylation because these modifications barely alter physical properties of target proteins and often are context dependent, transient, and substoichiometric. To reveal bona fide methylation events associated with specific PMT activities in native contexts, we developed the live‐cell Bioorthogonal Profiling of Protein Methylation (lcBPPM) technology, in which the substrates of specific PMTs are labeled by engineered PMTs inside living cells, with in situ–synthesized SAM analogues as cofactors. The biorthogonality of this technology is achieved because these SAM analogue cofactors can only be processed by the engineered PMTs—and not native PMTs—to modify the substrates with distinct chemical groups. Here, we describe the latest lcBPPM protocol and its application to reveal proteome‐wide methylation and validate specific methylation events. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Live‐cell labeling of substrates of protein methyltransferases GLP1 and PRMT1 with lcBPPM‐feasible enzymes and SAM analogue precursors Support Protocol : Gram‐scale synthesis of Hey‐Met Basic Protocol 2 : Click labeling of lcBPPM cell lysates with a biotin‐azide probe Alternate Protocol : Click labeling of small‐scale lcBPPM cell lysates with a TAMRA‐azide dye for in‐gel fluorescence visualization Basic Protocol 3 : Enrichment of biotinylated lcBPPM proteome with streptavidin beads Basic Protocol 4 : Proteome‐wide identification of lcBPPM targets with mass spectrometry Basic Protocol 5 : Validation of individual lcBPPM targets by western blot